Emerging Equity Markets in Middle Eastern Countries - El-Erian, Mohamed; Kumar, Manmohan (Washington, D.C. : International Monetary Fund, 1994)
Within a broad framework for analyzing portfolio capital flows to developing countries, the paper undertakes a comparative analysis of equity markets in six Middle Eastern countries. The analysis, based primarily on a range of quantitative indicators, identifies the principal characteristics of these markets, including relative to international comparators, and examines associated structural features. This, along with an analysis of the informational efficiency of selected markets in the region, provides a basis for the subsequent review of policies for enhancing the role of equity markets in the macroeconomy of Middle Eastern countries.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet